33.0k views
3 votes
Please help,, Consider the sequence of steps to solve the equation: 5(x - 3) = 7x2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x - 30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields Step 5.

1 Answer

2 votes

Summary: The solution to the equation (x - 3)(x + 9) = -27 is x = 0 and x = -6.

User Aren Hovsepyan
by
4.9k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.